ACE2 Receptor in the skin and Cutaneous Manifestations of SARS-Cov-2: A Review of the Literature - Pho, Denita Meiliani (HM Publisher, 2021)
A B S T R A C TSevere Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a newlydiscovered coronavirus that causes Coronavirus Disease 2019 (COVID-19). Theinteraction of SARS-CoV-2 transmembrane spike (S) glycoprotein with the humanangiotensin-converting enzyme-2 (hACE2) is the primary method of virus entry tothe cell. ACE2 is a transmembrane enzyme involved in the renin-angiotensin-aldosterone system. This enzyme plays pivotal roles in blood pressure regulationsand also electrolyte homeostasis. The expression of ACE2 in various skin cells hasbeen demonstrated in previous studies. Keratinocytes in the epidermis show anexceptionally high expression of ACE2. In addition to human skin, ACE2 is alsofound in animals’ tissues and were exceptionally high in cats and dogs’ skin andeyes. This finding suggests their obscure role in COVID-19 transmission. Cutaneoussymptoms of COVID-19 in humans exist as the consequence of ACE2 presence inthe skin. The possible mechanisms of COVID-19 clinical manifestations in the skinare upregulated innate immune human response, hypercoagulable state, and non-structural proteins in SARS-CoV-2. These processes are presented as differentdermatologic manifestations, which are maculopapular rash, papulovesicular rash,and livedo reticularis. This review aims to link the theoretical framework andpublished findings to establish the connection between ACE2 expression in skin andcutaneous manifestations of COVID-19.